Side effects of 1% cyclopentolate hydrochloride in children and adolescents attended at Centro Universitário FMABC - Valentino, Ianna Luiza Avelino; Fernandez, Celso Lopez; Fonseca, Fernando Luiz Affonso; Veiga, Glaucia Luciano da; Lima, Vagner Loduca (ABCS Health Sciences, 2020)
Introduction: It is known that vision disorders are within the context of public health problems. In childhood, during the neuropsychomotor development phase, visual changes are crucial, since there is a strong correlation between poor school performance and changes in acuity. For these reasons, ophthalmological examination in children, including refraction, is extremely important, aiming at the early diagnosis of diseases and possible refractive errors that may compromise the child's life and development. 1% cyclopentolate hydrochloride eye drops are the most used during ophthalmic clinical evaluation as a cycloplegic and mydriatic agent to assist in refractive examination. Objective: The ocular and systemic side effects of 1% cyclopentolate hydrochloride eye drops were studied in patients who underwent static refractive examination in the strabismus sector of the Ophthalmology Discipline of the Centro Universitário FMABC. Methods: A drop of 1% cyclopentolate is instilled in both eyes of each patient and the possible ocular and systemic signs and symptoms presented were observed after 40 minutes and 24 hours after instillation. Results: we expect to find ocular side effects more evident than systemic symptoms in the two evaluation times (40 minutes and 24 hours after instillation). All symptoms (ocular and systemic) are reversed spontaneously. Conclusion: The present study aims to show that the side effects observed by the topical (ocular) use of cyclopentolate eye drops 1% are few and present spontaneous reversal both from an eye point of view, as well as from a systemic point of view.